The immediate effect of alternate rapid maxillary expansions and constrictions on the alveolus: a retrospective cone beam computed tomography study - Narayan H. Gandedkar; Eric Jein-Wein Liou (SpringerOpen, 2018)
Abstract Background Rapid maxillary expansion reduced the expander's anchor teeth buccal alveolar bone thickness. However, the effects of alternate rapid maxillary expansions and constrictions (Alt-RAMEC) on the expander's anchor teeth alveolar thickness has not been assessed. The purpose of this retrospective study was to evaluate the effects of Alt-RAMEC on the alveolus surrounding the anchor teeth of a double-hinged expander. Methods Twenty-six individuals, including 12 males (11.5 ± 1.00 years) and 14 females (11.5 ± 0.90 years), who had double-hinged expander for 7 weeks of Alt-RAMEC and then 3 months of maxillary protraction, were included. Their cone beam computed tomography (CBCT) images taken 3-6 months before treatment (T0) and after 7 week of Alt-RAMEC (T1), were studied for the buccal alveolar bone thickness (BABT) and palatal alveolar bone thickness (PABT) of the expander's anchor teeth (first molars and first and second premolars) in four axial sections. The intra-class correlation coefficient, Dahlberg's formula, and paired t tests were used to analyze the method errors, and the intra-group changes of the BABT and PABT at T0-T1 were analyzed by paired t test (p < 0.05). Results The 7 weeks of Alt-RAMEC significantly reduced the BABT of the expander's anterior anchor teeth (0.54~ 70 mm, p < 0.05) and at the cervical region (0.14~ 0.25 mm, p < 0.05), but not at the apical region of the expander's posterior anchor teeth. The reduction of BABT by 7 weeks of Alt-RAMEC was within the scope of the initial BABT. On the opposite, the Alt-RAMEC significantly (p < 0.05) increased the PABT in the anterior anchor teeth and the cervical region of posterior anchor teeth. Conclusions A 7-week protocol of Alt-RAMEC with double-hinged expander for maxillary protraction might reduce the buccal alveolar bone thickness of the expander's anchor teeth, although the reduction is within the scope of initial alveolar thickness of the expander's anchor teeth.